Analisis Beban Kerja dan Motivasi Kerja terhadap Kinerja Karyawan pada PT. PLN (Persero) UP3 Banjarmasin - NUrul Afna; Hairul Anwar (P3M Politeknik Negeri Banjarmasin, 2022)
In the Digitalization era, some employees are required to be able to monitor work outside of the set working hours. This happens because the permanent employees have more jobs. The amount of workload felt by permanent employees has an impact on decreasing employee performance. To improve the performance of the company's employees, it is necessary to motivate permanent employees so that employee performance runs optimally. This study aims to determine the effect of workload and work motivation on employee performance at PT PLN (Persero) UP3 Banjarmasin. The method used in this study is quantitative and uses data collection techniques by distributing questionnaires to 73 employees as respondents using purposive sampling. After analyzing the data using multiple linear regression on workload and work motivation as independent variables and employee performance as the dependent variable, the results obtained partially that the workload has a significant negative effect on employee performance, which means that if the workload increases, employee performance will decrease, while employee motivation significant positive effect if employee motivation increases then employee performance will also increase. And the contribution of the two independent variables in this study is low at 19.8% while the remaining 80.2% is influenced by other variables outside of this study.